Analysis of Student Difficulties in Learning English Grammar in Junior High School Tunas Baru Jinseung - Silaban, Lisna Wanty; Adam Sulastri Manurung (JELLT (Journal of English Language and Language Teaching), 2025)
This study investigates the difficulties faced by students in learning English grammar at Tunas Baru Jinseung Junior High School, driven by concerns over consistently low grammar performance despite years of formal instruction. English grammar plays a central role in language acquisition, yet students often struggle with core aspects such as tenses, articles, and prepositions structures that differ significantly from those in Bahasa Indonesia. The aim of this study is to identify grammar-related challenges, analyze the contributing linguistic and psychological factors, and evaluate the influence of teaching strategies. The research addresses three main questions: the specific grammar difficulties students face, factors influencing these challenges, and the role of teaching methods in student grammar comprehension and performance. A qualitative method was applied, using purposive sampling to select six students and two English teachers involved in grammar learning. Data were collected through semi-structured interviews and classroom observations over two months. Interviews provided in-depth perspectives from participants, while observations allowed the researcher to examine classroom practices and student engagement in real-time. Data were analyzed using thematic analysis to identify recurring issues and barriers in grammar learning. The results indicate that structural differences between English and Bahasa Indonesia, coupled with teacher-centered methods relying heavily on memorization, hinder students' ability to grasp and apply grammar effectively. Psychological factors such as anxiety and low motivation further contribute to these difficulties. The study highlights the need for more communicative and task-based teaching approaches, emphasizing practical use of grammar in meaningful contexts. A supportive learning environment is also essential to foster motivation and reduce anxiety.